Сельскохозяйственные машины: краткий курс : учебное пособие / В. П. Гуляев - Гуляев Владимир Петрович (Лань, 2022)
Экземпляры: ТО (20220419) / Инвентарный номер: 1118824 / Цена: / Сис.шифр: 40.72 / Авт.знак: Г 94 / ГРНТИ: 68 / ББК: 40.72я7